(untitled) (Bangladesh Journal of Medical Biochemistry, 2014)
Patients with impaired glucose tolerance (IGT) are now considered as being pre-diabetic, which indicates their relatively high risk for developing diabetes mellitus associated with abnormal metabolic syndrome and cardiovascular diseases. However, dietary modification and physical exercise may play a critical role in this respect. To determine the influence of dietary modification and physical exercise in subjects with impaired glucose tolerance in Bangladesh, thirty three newly detected otherwise healthy subjects with IGT, aged 30-63 years, were randomly selected to participate in a 12 weeks diet and exercise program. Substantial improvement in glucose tolerance was observed at the end of 12 weeks particularly in middle aged subjects (41-50 years). Mean fasting blood glucose and 2 hr post load glucose value were reduced significantly. Glucose tolerance was reverted to normal in 66.7% of the participants, remained unchanged in 26.7% and deteriorated to diabetes in 6.7%. Significant reduction in serum total cholesterol, LDL cholesterol along with mild deterioration in HDL cholesterol and increase in triglyceride values were observed. It was found that the principles of ’prudent diet’ in combination with physical exercise are highly effective in improving glucose tolerance, lowering total cholesterol and LDL cholesterol in IGT subjects. DOI: http://dx.doi.org/10.3329/bjmb.v7i1.18575 Bangladesh J Med Biochem 2014; 7(1): 17-26